SOX Transcription Factors in Endothelial Differentiation and Endothelial-Mesenchymal Transitions - Yao, Yucheng; Yao, Jiayi; Boström, Kristina I. (Frontiers in Cardiovascular Medicine, 2019)
The SRY (Sex Determining Region Y)-related HMG box of DNA binding proteins, referred to as SOX transcription factors, were first identified as critical regulators of male sex determination but are now known to play an important role in vascular development and disease. SOX7, 17, and 18 are essential in endothelial differentiation and SOX2 has emerged as an essential mediator of endothelial-mesenchymal transitions (EndMTs), a mechanism that enables the endothelium to contribute cells with abnormal cell differentiation to vascular disease such as calcific vasculopathy. In the following paper, we review published information on the SOX transcription factors in endothelial differentiation and hypothesize that SOX2 acts as a mediator of EndMTs that contribute to vascular calcification.